**Answer: x = -1 , y = 8✔️**

**Step-by-step explanation:**

**-12x - 2y = -4 } Equation 1 **

**6x + 3y = 18 } Equation 2 **

<em>We can extract the value of x from the equation 2: </em>

6x + 3y = 18 } Equation 2

6x = 18 - 3y

x = (18 - 3y)/6 } Equation 2

<em>Then we can substitute this value of x in equation 1: </em>

-12x - 2y = -4 } Equation 1

-12·**(18 - 3y)/6** - 2y = -4

-36 + 6y -2y = -4

4y = -4 + 36

4y = 32

**y =** 32/4 **= 8**

<em>Now we can substitute this value of y in equation 2: </em>

x = (18 - 3y)/6 } Equation 2

**x =** (18 - 3·8)/6 = (18 -24)/6 = -6/6 **= -1**

**Answer: x = -1 , y = 8✔️**

<h3>

**Check **</h3>

<em>We can check this result by substituting these values of x and y into the equations: </em>

-12x - 2y = -4 } Equation 1

-12·(-1) - 2·8 = -4 ► 12 - 16 = -4✔️ checked!

6x + 3y = 18 } Equation 2

6·(-1) + 3·8 = 18 ► -6 + 24 = 18✔️ checked!

<h2><em>Spymore</em></h2>